EFFECT OF ACTIVATED ZEOLITE ON β-KAROTEN BLEACHED PALM OIL LEVELS - Syazana, Tengku Auni; Zulkania, Ariany (Journal TECHNO, 2022)
Palm oil is one of the Indonesian prima donna whose total national production is increasing every year. Palm oil can be used as a raw material for production of cooking oil products, industrial oil needs and energy sources. The base color of Crude Palm Oil (CPO) is due to the presence of a high β-carotene content in palm oil which can produce a red color in CPO. For this reason, it is necessary to bleach CPO. Most of the palm oil industry currently uses adsorbents as a pale material in the Bleaching process. This research does several things related to the process of making palm oil in general, the process is the production of adsorbents with activated adsorbents, removal of gum with H2SO4, bleaching process with adsorbents and analysis of bleaching oil (BPO). The experimental results show that zeolite can be used as an adsorbent for the bleaching process of palm oil. Zeolite has been activated by chemical methods using H2SO4 solution before being used as an adsorbent. From the experimental results, the best results for the application of β-carotene were obtained from 3% activated zeolite with 15% by weight zeolite.